Fiscal policy and growth in a panel of EU countries over 1995-2017 - Ilias Kostarakosa; Petros Varthalitis (The Economic and Social Research Institute (ESRI), 2020)
This paper reassesses the predictions of the standard Barro-type endogenous growth models drawing on recent developments in the panel time series literature. In particular, we employ the Common Correlated Effects (CCE) estimator developed in Pesaran (2006) and estimate the effects of fiscal policy for a panel of EU countries using annual data from 1995 to 2017. Our results provide strong support for the predictions of the standard endogenous growth model. More importantly, the CCE estimation generates significantly larger effects of fiscal policy on growth with respect to the other widely used estimation methods. Our comparative analysis indicates that estimation methods which ignore the heterogeneous impact of unobserved common factors across countries could lead to a significant underestimation of the effects of fiscal policy on growth.
Keywords: H50; O40; 330; long-run growth; fiscal policy; unobserved common factors; cross-sectional dependence